The use of the epistemic and deontic modality in the modal verb “can” between English native and Spanish non-native students in the written discourse - Gil Bonilla, John Fredy (Journal of Artistic Creation and Literary Research, 2025)
Modality has been a field of deep study by semantictians and pragmatists. This field has been of interest for professors of Complutense University of Madrid as Marta Carretero (1995) and Angela Downing (2015), among others. The present study aims to analyze the use of the modal verb “can” and its counterparts “could”, “cannot” and “could not” in written texts by English native students (NS) and Spanish non-native students of English (NNS). More specifically, the study tries to answer the following research questions: (1) Are the modals under analysis used more frequently by NS or NNS? and (2), Do NS or NNS use modality differently regarding the degree of formality? To this purpose, two subcorpora (academic and informal texts) were gathered by means of analyzing online journals and online chats, rendering a total of 243 modals in NS and 282 in NNS texts. The analysis of the data reveals that a high frequency of modality depends on a high degree of formality.